Introducing Alaska to Finns: A marketing strategy for improving Ketchikan's visibility in Finland - Samsten, Piia (HAAGA-HELIA ammattikorkeakoulu, 2013)
This thesis was comissioned by the Ketchikan Visitors Bureau. This study is a marketing strategy of how Ketchikan should increase visibility and promote itself in Finland. The marketing strategy studies, whether there is a future for further planning and action. The aim was to analyze Alaska and Ketchikan markets and then based on the information create the marketing strategy. The study includes destination analysis, theory about marketing strategy, statistics about the visitors of Ketchikan and Alaska and European markets, small research about the image of Alaska in Finland and the actual marketing strategy. This study used research methods like interview and observing. Interview was executed in Finland and observing happened both in Finland and Ketchikan to accomplish the goal. Goal for this study was to get answers to the questions of what kind of markets exist in between Alaska and Europe, what kind of tourists visit in Ketchikan or Alaska, what Finnish people know about Alaska, have Ketchikan or Alaska already some promotion in Finland, how should Ketchikan promote itself and increase the visibility in Finnish markets and what will be the future of Ketchikan or Alaska in Finland or European markets. Alaska is an unknown destination in Finland and this affects the markets. Some tour operators in Finland are organizing cruises or tour packages to Alaska, but only few people travel to Alaska. If Ketchikan want to increase its popularity it should focus on developing the Internet visibility by developing better searh engines, websites and social networking sites. Ketchikan could also create new relationships with Finnish tour operators and focus on developing existing co-operation between travel guide publishers and existing tour operators in Finland.